Chapter The ISPRA geodatabase for monitoring and analysis of the state of the italian coasts: an example of its application to the Rocchette - Castiglione della Pescaia coast line - D'Ascola, Filippo (Monitoring of Mediterranean Coastal Areas: Problems and Measurement Techniques, 2022)
The Italian Institute for Environmental Protection and Research (ISPRA) has developed the Geodatabase "Linea di Costa". that allows to perform spatial analysis on the recorded geometrical elements, and to provide a periodic update on the evolution of the coastline. The main objective of this work is to highlight the potential of a continuously updated geodatabase over time in monitoring and analysing the state of the coasts at a local level, presenting one of several case studies carried out by ISPRA, following specific requests related to local coastal dynamics received from the stakeholders.